Evidence-informed pedagogy and the enhancement of student employability - Yorke, Mantz; Knight, Peter (Teaching in Higher Education, 2007)
Claims are frequently made that practice should be based on evidence. However, the nature of what should count as ‘evidence’ depends on purpose and context. In the case of curriculum development, decisions may rest on local and provisional evidence. This article takes an area of contemporary political interest—enhancing student employability—and illustrates the point with two examples of the use of survey methods for pedagogical purposes.